(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The growing addition of greenhouse gases to the environment, as well as the depletion of petroleum supplies, pique the academics’ interest in developing innovative techniques for generating clean, long-term power from natural sources Many of these resources exist in reality and are ready to assist mankind at any time. Among the several renewable energy sources accessible, windy, solar, and biomass power are the most common. The emphasis of this study is on biogas technology, which is a highly appealing technique to use biomass sources to meet partial energy needs. This paper discusses the overview of anaerobic digestion, Stages of anaerobic digestion, Factor affecting anaerobic digestion and types of anaerobic digestion Biogas systems may benefit consumers in a variety of ways while also helping to safeguard the environment. Biogas is produced by the anaerobic digestion of organic materials in biogas systems. Biodegradable biomass materials may be fed into biomass digesters in any quantity. Typical biomasses include agriculture waste, crop remnants, livestock wastes, forest residues, and other wastes.